Phrases in literary contexts: patterns and distributions of suspensions in Dickens’s novels - Mahlberg, Michaela; Smith, Catherine; Preston, Simon (John Benjamins Publishing, 2013)
This paper addresses relations between lexico-grammatical patterns and texts. Our focus is on a specific linguistic unit, the ‘suspended quotation’ (or ‘suspension’), which has received particular attention in Dickens studies. The suspended quotation refers to an interruption of a fictional character’s speech by the narrator with a sequence of at least five words. We show how corpus linguistic methods can help to systematically study suspensions in a corpus of Dickens’s novels: we investigate relationships between patterns of body language presentation and suspensions; we consider the distribution of suspensions across novels; and we illustrate how patterns in suspensions relate to meanings of reporting verbs. Overall, we argue that suspensions are discernible units that contribute to meaningful patterns in narrative prose.